An Ultrasound‐Driven Bioadhesive Triboelectric Nanogenerator for Instant Wound Sealing and Electrically Accelerated Healing in Emergencies. Issue 12 (8th February 2023) - Meng, Xiangchun; Xiao, Xiao; Jeon, Sera; Kim, Dabin; Park, Byung‐Joon; Kim, Young‐Jun; Rubab, Najaf; Kim, SeongMin; Kim, Sang‐Woo
Abstract: A bioadhesive triboelectric nanogenerator (BA‐TENG), as a first‐aid rescue for instant and robust wound sealing and ultrasound‐driven accelerated wound healing, is designed. This BA‐TENG is fabricated with biocompatible materials, and integrates a flexible TENG as the top layer and bioadhesive as the bottom layer, resulting in effective electricity supply and strong sutureless sealing capability on wet tissues. When driven by ultrasound, the BA‐TENG can produce a stable voltage of 1.50 V and current of 24.20 µA underwater. The ex vivo porcine colon organ models show that the BA‐TENG seals defects instantly (≈5 s) with high interfacial toughness (≈150 J m −2 ), while the rat bleeding liver incision model confirms that the BA‐TENG performs rapid wound closure and hemostasis, reducing the blood loss by about 82%. When applied in living rats, the BA‐TENG not only seals skin injuries immediately but also produces a strong electric field (E‐field) of about 0.86 kV m −1 stimulated by ultrasound to accelerate skin wound healing significantly. The in vitro studies confirm that these effects are attributed to the E‐field‐accelerated cell migration and proliferation. In addition, these TENG adhesives can be applied to not only wound treatment, nerve stimulation and regeneration, and charging batteries in implanted devices. Abstract : A novel strategy of instant wound sealing and electrically assisted wound healing by an ultrasound‐driven bioadhesive triboelectric nanogenerator is used to treat wounds in an emergency, to avoid serving hemostasis and infection, and the electrical stimulation driven by ultrasound promotes skin wound healing significantly via cell migration and proliferation, being a potential first‐aid rescue and self‐help method of portable medical devices.